A Juridical Analysis of Legal Sanctions Against Unlicensed Medical Practice - P.Darmadi; Q.Efendi (International Medical Journal Corp. Ltd, 2024)
Introduction: Unlicensed medical practice poses a critical threat to public health, patient safety, and the integrity of the healthcare system. Despite stringent regulatory frameworks, rogue practitioners continue to exploit vulnerable patients, necessitating a rigorous legal examination of existing enforcement mechanisms. Methods: This study employs a normative juridical research method, analyzing primary legal materials such as health statutes and secondary sources including judicial precedents and legal literature. Results: The analysis reveals that while statutory criminal and administrative sanctions are robust on paper, implementation is frequently hindered by weak inter-agency enforcement, ambiguous statutory interpretations regarding alternative medicine, and a lack of public legal literacy. Discussion: The discussion integrates a comprehensive literature review on medical jurisprudence, contrasting strict liability with fault-based culpability, and examines how enforcement gaps create opportunities for illicit operators. It underscores that current penal measures often treat symptoms rather than the systemic root causes of unauthorized practice, highlighting a significant divergence between law in books and law in action. Conclusions: This study concludes that statutory legal sanctions must be accompanied by proactive, digitized monitoring and enhanced public education.